A family of novel RCM rotational compliant mechanisms based on parasitic motion compensation. (February 2021) - Huo, Tonglong; Yu, Jingjun; Zhao, Hongzhe; Wu, Haoran; Zhang, Yuan
Highlights: A family of RCM rotational compliant mechanisms with high accuracy is proposed. Parasitic motion is compensated by center shift of generalized cross-spring pivot. A compensation model is developed to provide design insights. FEA comparison shows the proposed mechanisms greatly reduce parasitic motion . Abstract: RCM (remote center of motion) rotational compliant mechanisms are of great use in precision machines, especially when a pure rotation about a virtual center is required. The accuracy of the mechanisms is an essential consideration for mechanical design in applications. In this paper, a family of RCM rotational compliant mechanisms is designed to compensate parasitic motion of the trapezoidal four-bar mechanism by taking advantage of center shift of generalized cross-spring pivot. Firstly, parasitic motion of the trapezoidal four-bar mechanism is modeled based on kinematics analysis. Then, the compensation principle for the parasitic motion is proposed on the basis of compensation motion analysis. In addition, nine topological structures of the RCM rotational compliant mechanisms are presented by adopting generalized cross-spring pivot as a building block, and compensation model for geometric parameters of these flexural pivots are obtained. Furthermore, the validation and effectiveness of the proposed method are verified by finite element analysis (FEA). The results show that the RCM rotational compliant mechanism proposed in this paper is capable of offering an ultra-high-precision rotation and providing a promising application prospect in precision engineering.